The blood supply of the human spinal cord at birth: a report on a micro-dissection study of 27 foetal and neonate cadavers - Dommisse, George Frederick (Division of General Surgery, 2020)
The Vascular system of the human spinal cord at birth has been investigated, and a report is submitted on the detailed pattern of the arterial and arteriolar vessels in 27 cadavers. In 21 instances, the anterior median spinal arterial trunk and in 9 instances the postero-lateral spinal arterial trunks have been recorded. Selection of cadavers has been on the basis of the absence of obvious congenital deformity or disease of the spine and spinal cord. Particular attention has been paid to the feeder arteries which contribute to the main longitudinal channels, both anteriorly and posteriorly. The number of feeder vessels, their ;.., sources of origin .and their approximate size~ have been determined. In 21 specimens the anterior vessels have been recorded and charted in detail. (Plates I - VII). In 9 specimens the posterior vessels have been recorded and the detailed charts of 3 of the latter are presented. (Plate X, p.46).